IMMUNOLOGICAL MONITORING OF SLOW DOWN OSTHEOGENESIS - O. V. Berdugina (Медицинская иммунология, 2014)
Abstract. We have performed clinical and immunological investigation in the patients with trauma of face bones before and after stable mandibular ostheosynthesis. Blood samples for analysis were taken upon admission of the patient to clinics, and following treatment (3, 10, and 1-2 months). The patients with initially retarded bone consolidation exhibited low levels of monocytes and lactoferrine before surgical treatment. It was shown that the consecutive stages of bone regeneration (inflammation, osteoblastic proliferation, collagenogenesis, and ossification) are accompanied by certain changes in immune parameters. In particular, we observed increased levels of IgМ, TNF, and activation of leucopoiesis after treatment. The results obtained allow us of discriminating some natural reactions of immune system in cases of normal and retarded bone consolidation. For each of these criteria, diagnostic sensitivity and informativity of tests are calculated, thus providing an opportunity to predict retarded consolidation in surgical treatment of the face bones. (Med. Immunol., 2007, vol. 10, N 4-5, pp 371-388).